Democratic decentralization and disempowerment of traditional authorities under Ghana's local governance and development system: a spatio-temporal review. Issue 3 (2nd September 2017) - Adjei, Prince Osei-Wusu; Kwaku Busia, Abrefa; Bob-Milliar, George Meyiri
Abstract: In this paper, we argue that democratic decentralization defined as the transfer of power and resources from central government to lower units of government to deliver downwardly accountable and responsive local representation does not entirely produce stronger local institutions for mass participation, good local governance and community development. This is supported with selected cases from Ghana to demonstrate how in the name of decentralization and effective local governance, spaces have been created to subvert and disempower traditional authorities and their institutions thereby affecting their relevance and active participation in local governance and development through time and across space.